Hvem er “vi” egentlig? : Om Paulus’ brug af flertalsformer i Galaterbrevet - Friis, Martin (Dansk Teologisk Tidsskrift, 2021)
This article explores Paul’s use of first-person plural forms in Galatians (specifically Gal 2:15-16; 3:13-14; 3:23-29; 4:1-7 and 4:26 and 31). Proponents of the ‘Sonderweg perspective’ and of ‘the radical new perspective on Paul’ argue that Paul uses these forms as a rhetorical device. He seeks to identify himself with his non-Jewish audience without implying that he himself nor his fellow Jews share in ‘our’ (i.e., non-Jewish) experiences. In opposition to this view, this article presents a ‘new Pauline perspective’ understanding of Paul’s use of ‘we’/’our’. Instead of assuming that his ‘we’ should be construed as ‘you’, it is argued that it ought to be seen as an inclusive ‘we’. Throughout his argumentation in Galatians Paul actively alludes to experiences that he himself and his fellow Christ-believing Jews have partaken in, including the reception of the Spirit, adoption, and liberation from slavery of the flesh and from being ‘under the Law’.